Qatar National Diabetes Strategy for the growing diabetes pandemic (2016-2022) - are we there yet? - Shah, Benazir (International Journal of Research in Medical Sciences, 2024)
Diabetes Mellitus (DM) is increasingly recognized as a major public health challenge with 422 million people suffering worldwide in 2014. Awad et al anticipated that by 2050, that DM prevalence and incidence in Qatar will rise significantly, emphasizing the rapidly expanding need for health care resources to treat the condition and highlighting the necessity of intervention techniques for treatment and prevention that are specific for each nationality in Qatar.